5G Impacts, Internet of Things (IoT) and Businesses in Developing Countries - Tom, Teckshawer (Technium Social Sciences Journal, 2023)
This study addresses the ramifications of 5G technology for enterprises in developing countries and how it affects the Internet of Things (IoT). The IoT ecosystem is expected to see considerable improvements in connectivity, speed, and capacity with the introduction of 5G networks. The potential advantages and difficulties of integrating 5G technology into the IoT landscape are discussed in this study, along with how it might change several industries in developing nations. This research also highlights how 5G technology might boost IoT capabilities through higher device densities, lower latency, and faster data transmission rates. Additionally, it looks into the particular ramifications for enterprises in underdeveloped countries, taking into account the difficulties with infrastructure, affordability, and the digital divide that these countries confront. It also discusses the potential hazards and obstacles to the deployment of 5G, such as the requirement for suitable legal frameworks, security precautions, and talent development. The results of this study help to improve awareness of the potential effects of 5G technology on the IoT landscape in developing countries and offer guidance for stakeholders, enterprises, and policymakers in properly using its advantages.